Mochammad Natsir dan Pemikiran Ekonomi Ummat 1950-1960 - Emalia, Imas (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2013)
Abstract This article is intended as an attempt to reconstruct the history of thought from a figure of the famous politician who is soft, firm, and islamic behave, Mochammad Natsir. His thoughts about the economy of the Muslims is as his fight in Indonesia people’s destinies take notice, especially Muslims. During his life in pursuit of economic Natsir Mochammad Muslims either when he politicking, of community, and preaching. Related to the economic development of this Ummah, Mochammad Natsir championed economic development via the Ummah Party Mayumi, the largest Islamic Ummah as the party at the time. In discussing character Mochammad Natsir, has always been in the political discussion, whether its action in politics or also his idea about politics that inevitably associated with Islam, very little discussion about his thinking in the field of Economics, but it turns out that economics is concerned Natsir Mochammad Ummah, generally the people of Indonesia. His thoughts on the economy is very inspiring and uplifting for the people of Indonesia to be able to maintain his life struggling to avoid poverty, squalor, misery, and suffering due to the behavior of those who blackmail her life wander the property. His idea about Islamic economic development Mochammad Natsir Ummah who looks at and strive to let the Muslims during the post-revolution until the 1960 's can live peaceful, prosperous, far from suffering, poverty, misery, and always pay attention to the messages from the teachings of Islam. Message from thinking this is about Mochammad Natsir human duty to care for and respect each other, because that is the nature of a human being as an independent creature who had to work hard in the face of the Earth to avoid poverty. This paper, entitled